IMF Committee on Balance of Payments Statistics : Annual Report 2009. (Balance of Payments Statistics; Balance of Payments Statistics, 2010)
This Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) for 2009 provides an overview of recent trends in balance of payments and international investment position statistics. The Annual Report also discusses the Committee's work program during 2009 and reviews the issues the Committee plans to address in the coming year.